Case report: Local anesthesia with lidocaine infiltration for extended-release buprenorphine therapy - Azar, Pouya; Kim, Jane J.; Rohani, Ella; Newman-Azar, Dayyon; Narimani, Matin; Machado, Jessica; Li, Victor W. (Frontiers in Psychiatry, 2025)
BackgroundExtended-release buprenorphine (BUP-XR) is a once-monthly subcutaneous injection for the treatment of opioid use disorder. Injection-site pain is a common adverse event reported with BUP-XR administration. Notwithstanding the advantages of BUP-XR, subjective pain and anxiety associated with injections can compromise patients’ willingness to receive treatment. Lidocaine is an amide-type agent and sodium channel blocker commonly used for local and regional anesthesia in various fields of medicine.Case presentationWe present two cases involving lidocaine infiltration to the induction phase of BUP-XR therapy in an outpatient setting. Prior to the intervention, 2 mL of 1% lidocaine was infiltrated subcutaneously at the sites of the planned needle insertion for a numbing effect. The following BUP-XR therapy was well tolerated by both participants and reported as a painless procedure.ConclusionsLidocaine infiltration may be a feasible way to successfully initiate and provide BUP-XR therapy to those who may be deterred by injection-related risks. Our cases describe how lidocaine can be useful in mitigating injection-site pain and encouraging greater uptake, and in turn, greater retention in opioid agonist therapy.